Re-Imaginings: A Mother’s Remembrance of her Murdered Daughter - Savarese, Josephine L. (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
We spent a day together when She was young. We loved lilacs—they are so beautiful. We found a lilac bush filled with blooms and gathered as many as we could. We had lilacs in every room. Her body was found after two months buried in an isolated wooded area. RCMP officers were led to the clandestine burial site by Him.